Heat Mediated Synthesis of Silver Nanoparticles Using Citrus limon (Lemon) Extract - Prathna1, T.C.; M. Raichur1, Ashok; Ch, N.; Mukherjee3, Amitava (Asian Journal of Chemistry, 2013)
In the present study, silver nanoparticles were rapidly synthesized by treating silver ions with Citrus limon (lemon) extract at higher temperature. The effect of process parameters like reductant concentration, mixing ratio of the reactants, concentration of silver nitrate and heating time period were studied. The formation of silver nanoparticles was confirmed by surface plasmon resonance as determined by UV-visible spectra in the range of 400-500 nm. X-ray diffraction analysis revealed the distinctive facets (111, 200, 220, 222 and 311 planes) of silver nanoparticles. Nanoparticles below 50 nm with spherical and spheroidal shape were observed from microscopic studies. The study offers a rapid method to synthesize silver nanoparticles within ten minutes of interaction with the bio-reductant.